2018
DOI: 10.1038/s41372-018-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of altitude on screening for critical congenital heart disease

Abstract: Screening infants for critical cardiac defects at altitude is complicated by the increased false positive screens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
7
1
4
Order By: Relevance
“…A multicenter study of various altitudes conducted by Paranka et al, also showed an increase in the positive screen rate with increasing altitude. However, when using the AAP-Kemper passing threshold of ≥95%, only 6% of newborns >6000 ft had a positive screen [5]. Our higher false positive rate compared to Paranka et al findings are likely due to us only evaluating the first SpO 2 measurement as opposed to the overall screening algorithm.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…A multicenter study of various altitudes conducted by Paranka et al, also showed an increase in the positive screen rate with increasing altitude. However, when using the AAP-Kemper passing threshold of ≥95%, only 6% of newborns >6000 ft had a positive screen [5]. Our higher false positive rate compared to Paranka et al findings are likely due to us only evaluating the first SpO 2 measurement as opposed to the overall screening algorithm.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, ways to further improve the algorithm, including at higher altitude, have been noted [12]. Hospitals at high altitude have noted increased false positive rates using the standard AAP SpO 2 thresholds leading to a significant increase in the number of unnecessary echocardiograms required [4,5]. Considering the most recent updated CCHD algorithm now only requires one repeat measurement as opposed to two before classifying as a failed screen and potentially triggering an echocardiogram, the pass threshold at high altitude is even more crucial to clarify [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Likewise, the frequency of a positive screen increased with increasing altitude from 0.2% for infants born at sites at or less than 2000 ft to 6% for infants born at sites above 6000 ft. Enrollment at 8163 ft was stopped after enrolling 65 infants because of a very high false-positive rate (35%). 14 Altitude affects newborn saturations by causing delayed transition from fetal to neonatal circulation because of lower partial pressure of oxygen, restricting the degree of expected pulmonary vasodilation. With elevated pulmonary vascular resistance, pulmonary artery to aorta shunting via the patent ductus arteriosus causes decreased post-ductal saturations.…”
mentioning
confidence: 99%